2019
DOI: 10.1007/s12471-019-01352-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of balloon pulmonary angioplasty in chronic thromboembolic pulmonary hypertension in the Netherlands

Abstract: Background Balloon pulmonary angioplasty (BPA) is an emerging treatment in patients with chronic thromboembolic pulmonary hypertension (CTEPH) and chronic thromboembolic disease (CTED). We describe the first safety and efficacy results of BPA in the Netherlands. Methods We selected all consecutive patients with inoperable CTEPH and CTED accepted for BPA treatment who had a six-month follow-up in the St. Antonius Hospital in Nieuwegein and the Amsterdam University Medical Center (UMC) in Amsterdam. Functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 23 publications
(34 reference statements)
2
20
0
Order By: Relevance
“…Table 1 outlines the registries published to date (excluding, where possible, those covering the same population more than once). [ 22 36 ]…”
Section: Balloon Pulmonary Angioplastymentioning
confidence: 99%
“…Table 1 outlines the registries published to date (excluding, where possible, those covering the same population more than once). [ 22 36 ]…”
Section: Balloon Pulmonary Angioplastymentioning
confidence: 99%
“…[ 6 ] Recent study found that BPA could significantly improve pulmonary hemodynamics and exercise capacity of patients with inoperable CTEPH, and better safety was guaranteed. [ 7 ] Furthermore, a systematic review assessed the efficacy and safety of BPA for CTEPH, and the results showed that BPA could improve hemodynamics and increase survival rate. [ 8 ] On the other hand, such targeted therapies as soluble guanylate cyclase stimulators (riociguat), PDE-5 inhibitors (sildenafil), endothelin receptor antagonists (bosentan and macitentan) and prostacyclin analogues (iloprost, beraprost, and treprostinil) had shown better effects in patients with CTEPH.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Meanwhile, various centers around the world have published their initial results. [34][35][36][37][38][39] In TABle 1, we summarized initial experiences beginning with the United States group in 2001, then presenting the Japanese registry (7 centers) and the first European groups. It becomes obvious that especially the hemodynamic improvement is usually less pronounced than in Japanese studies.…”
mentioning
confidence: 99%
“…Further, balloon size is slightly underestimated to avoid pulmonary artery rupture. The intervention is performed under fluoroscopy guidance, and numerous centers use digital subtraction angiography to document the postinterventional result [29][30][31][32][33][34][35][36][37][38][39][40] (FiGuRe 1). Meanwhile, various refinements have been suggested such as the use of optical coherence tomography, 48 dyna-computed tomography, 49 as well as pressure wires and intravascular ultrasound.…”
mentioning
confidence: 99%
See 1 more Smart Citation